HGFDB: a collective database of helmeted guinea fowl genomics. (8th January 2021) - Li, Xuzhen; Li, Zhi; Shen, Quankuan; Pan, Yunbin; Dong, Xiao; Xu, Zetan; Duan, Shengchang; Li, Yunfei; Du, Yuan; Chen, Shanshan; Ma, Zhaocheng; Dong, Yang
Abstract: As a vigorous and hardy and an almost disease-free game bird, the domestic helmeted guinea fowl ( Numida meleagris, hereafter HGF) has attracted considerable attention in a large number of genetic study projects. However, none of the current/recent avian databases are related to this agriculturally and commercially important poultry species. To address this data gap, we developed Helmeted Guinea Fowl Database (HGFDB), which manages and shares HGF genomic and genetic data. By processing the data of genome assembly, sequencing reads and genetic variations, we organized them into eight modules, which correspond to 'Home', 'Genome', 'Re-sequence', 'Gene', 'Variation', 'Download', 'Tools' and 'Help', HGFDB provides the most comprehensive view of the HGF genome to date and will be relevant for future studies on HGF structural and functional genomics and genetic improvement. Database URL: http://hgfdb.ynau.edu.cn/